Five new South American species of Myrcia s.l. (Myrtaceae) - Santos, Matheus Fortes; Lucas, Eve; Sano, Paulo Takeo (Phytotaxa, 2015)
Five new species of Myrcia s.l. are described and illustrated: Myrcia ascendens (related to Myrcia densa), Myrcia attenuata (related to Myrcia bicolor), Myrcia costeira (related to Myrcia bicarinata), Myrcia rupestris (related to Myrcia lenheirensis) and Myrcia subterminalis (related to Myrcia bicolor). The new species occur in the Brazilian Atlantic Forest (M. costeira and M. subterminalis), the Espinhaço range in Brazil (M. ascendens and M. rupestris) and the eastern Guiana Shield in French Guiana (M. attenuata). Additionally, species are discussed regarding distribution, habitat, phenology and taxonomic affinity.